Desain Model Si Raga Untuk PembelajaranPencak Silat: Studi Pendahuluan - Rochmad C Ganny; Aisah R. Pomatahu; Mirdayani Pauweni (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The purpose of this study is to design the SI RAGA model in martial arts learning to enhance students’ motivation in learning pencak silat in physical education classes. The research method employed is a research and development approach, involving the design of a learning model framework based on the pencak silat competition category and integrating rational, active, enjoyable, and safe learning strategies. The results indicate that the SI RAGA model is an innovative learning model grounded in deep learning principles, namely awareness, meaning, and joy, which can support the improvement of students’ motivation in learning pencak silat. In conclusion, the SI RAGA model can serve as an effective alternative learning model in martial arts education, particularly pencak silat, as it integrates aspects of safety, active participation, and enjoyable learning aligned with deep learning principles. Keywords: Design, Model, Learning, Pencak Silat, SI RAGA